Success in cc skiing: no longer just a question of a high aerobic capacity - Saltin, B. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
About the effects of the "dramatic changes" which took place in cross-country skiing in the last years (sprint races, mass starts, skating, ...) and the consequences for training.